PEMANTAUAN KEKERUHAN DAN SUHU AIR KOLAM IKTIOTERAPI BERBASIS MIKROKONTROLER PADA MITRA RULE ATHALLAH BANYUASIN - Franklin Khobir; Muhammad Agus Triawan; Arif Prambayun; Yulian Mirza; M. Aidil Fikka S (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Water quality in fish farming plays an essential role in maintaining the health and survival of the fish. The same applies to ichthyotherapy ponds, where water quality not only affects the survival of therapy fish but also influences the effectiveness of the therapy for users. This study analyzes real-time variations in water turbidity and temperature as physical parameters using a microcontroller-based monitoring system implemented at Rule Athallah, Banyuasin. The turbidity and temperature sensor data from ichthyotherapy pool water sample were continuously collected every 0.6-second intervals for approximately 4.57 hours. The turbidity sensor recorded a value of 0.0 NTU, indicating that the ichthyotherapy pond water was relatively clear with minimal suspended particles during the observation period. This NTU value remains within the optimal range for ichthyotherapy activities. Meanwhile, the water temperature remained stable, ranging between approximately 23.9°C and 24.2°C. These findings suggest that the developed system can serve as a reliable tool for automatic and measurable monitoring of ichthyotherapy pond water quality.